Novel role and mechanism of glutathione peroxidase-4 in nutritional pancreatic atrophy of chicks induced by dietary selenium deficiency - Jia-Qiang Huang; Yun-Yun Jiang; Fa-Zheng Ren; Xin Gen Lei (Redox Biology, 2022)
Nutritional pancreatic atrophy (NPA) is a classical Se/vitamin E deficiency disease of chicks. To reveal molecular mechanisms of its pathogenesis, we fed day-old chicks a practical, low-Se diet (14 μg Se/kg), and replicated the typical symptoms of NPA including vesiculated mitochondria, cytoplasmic vacuoles, and hyaline bodies in acinar cells of chicks as early as day 18. Target pathway analyses illustrated a > 90% depletion (P < 0.05) of glutathione peroxidase 4 (GPX4) protein and up-regulated apoptotic signaling (cytochrome C/caspase 9/caspase 3) in the pancreas and(or) acinar cells of Se deficient chicks compared with Se-adequate chicks. Subsequently, we overexpressed and suppressed GPX4 expression in the pancreatic acinar cells and observed an inverse (P < 0.05) relationship between the GPX4 production and apoptotic signaling and cell death. Applying pull down and mass spectrometry, we unveiled that GPX4 bound prothymosin alpha (ProTalpha) to inhibit formation of apoptosome in the pancreatic acinar cells. Destroying this novel protein-protein interaction by silencing either gene expression accelerated H2O2-induced apoptosis in the cells. In the end, we applied GPX4 shRNA to silence GPX4 expression in chick embryo and confirmed the physiological relevance of the GPX4 role and mechanism shown ex vivo and in the acinar cells. Altogether, our results indicated that GPX4 depletion in Se-deficient chicks acted as a major contributor to their development of NPA due to the lost binding of GPX4 to ProTalpha and its subsequent inhibition on the cytochrome c/caspase 9/caspase 3 cascade in the acinar cells. Our findings not only provide a novel molecular mechanism for explaining pathogenesis of NPA but also reveal a completely new cellular pathway in regulating apoptosis by selenoproteins.